Emerging strontium isoscapes of Anatolia (Türkiye): new datasets and perspectives in bioavailable 87Sr/86Sr baseline studies - Yazıcıoğlu, G. Bike; Meiggs, David C.; Davis, Maxwell; Pilaar Birch, Suzanne E. (Frontiers in Environmental Archaeology, 2025)
IntroductionThe use of strontium isotope ratio (87Sr/86Sr) analysis in ancient mobility studies in the archaeology of Anatolia (modern Türkiye) has steadily grown since the early 2010s. However, a coherent map of the isotopic variability of bioavailable Sr (isoscape) does not exist for the region and the paucity of baseline data that is necessary for the interpretation of archaeological data significantly constrains the heuristic power of this methodology in Anatolian archaeology. Baseline and “local range” determination in previous studies have relied on geology maps or various sample types from very limited areas in site-centered mobility studies, and the use of predictive modeling for isoscape reconstruction at regional scales has just begun in Türkiye.MethodsIn this study, we discuss current methodologies in Sr isoscape reconstruction including the recent open-access R-script and global database developed for modeling bioavailable 87Sr/86Sr isoscapes and we present a review of extant 87Sr/86Sr analyses and baseline studies in Anatolian archaeology. We combine all published baseline 87Sr/86Sr data from Türkiye with our unpublished 87Sr/86Sr data from proxy samples (plants and snail shells) from central Anatolia, and by incorporating this data (n = 688) into the global database (where data from Türkiye is currently lacking), we create a modeled 87Sr/86Sr isoscape of Türkiye utilizing the R-script and we calculate the predicted standard error for this isoscape.Results and discussionThis study demonstrates how additional empirical data serves to improve the Türkiye section of the global model using kriging and random forest regression (RFR) techniques and it discusses how the uneven distribution of data impacts the resultant isoscape map. In closing, we comment on beneficial avenues for mobility studies in under-researched periods and regions in Anatolia.